Consumer Perception and Attitude towards Credit Card Usage:: A Study of Pakistani Consumers - Ahmed, Afshan; Amanullah, Ayesha; Hamid, Madiha (Journal of Comparative International Management)

(untitled) (None, 2009)
Consumer financing have become increasingly important in the private sector of Pakistan for the last two decades. With the new reforms in the banking sector, the marketing of financial products has become very competitive, creating a need for strategizing the marketing efforts. This study investigates the shift of Pakistani consumers towards the use of plastic money, with emphasis on credit cards. A survey of consumers holding (at least) one or no credit card were used for data collection. Variables related to demographics such as age, income level and gender have also been taken into consideration. This study makes (the) use of descriptive variables in terms of analyzing the general attitude about the use of credit cards and the factors contributing towards the selection of (a) one particular credit card over the other. A positive relationship has been found between the income level of a person and his/her possession of the credit card. While making the choice of a credit card the trust in a particular brand name seems to hold a very significant importance in the selection of a credit card, instead of the logo of Visa or Master card. The profession of the person seems to play a very interesting role with their behavior towards credit cards. Our study shows that the bankers hold negative attitude towards the use of a credit card. The moderating variables include the marketing campaign of a particular bank, sales teams support, openness from retailers for accepting credit card instead of cash, knowledge about the true interest rate imposed by the banks and the concept of Islamic mode of financing, etc. Based on our observations, suggestions have also been made for managers to refine the target market.